2014
DOI: 10.1002/ceat.201400209
|View full text |Cite
|
Sign up to set email alerts
|

Designing Printable Medicinal Products: Solvent System and Carrier‐Substrate Screening

Abstract: More flexible yet robust manufacturing solutions are needed in the pharmaceutical industry. Tablet compaction is no longer the obvious choice for commercialscale processing of innovative drug delivery systems. Engineering solutions have gained wide attention in the pharmaceutical industry. Technical innovations within printing are considerable solutions for future product design. Printable medicinal products of a model compound are designed and an analytical approach for imaging the model compound in the print… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Genina et al (2012) found that riboflavin, which is highly soluble in water, precipitated in the presence of polyethylene glycol; glycerol was thus used instead. An additional benefit of using glycols is their role in reducing the evaporation of the solvent, as they act as humectants (Raijada et al, 2014). Rapid evaporation of the solvent can lead to the clogging of the nozzle due to the precipitation of the components of the formulation at the nozzle's tip.…”
Section: Before Printingmentioning
confidence: 99%
“…Genina et al (2012) found that riboflavin, which is highly soluble in water, precipitated in the presence of polyethylene glycol; glycerol was thus used instead. An additional benefit of using glycols is their role in reducing the evaporation of the solvent, as they act as humectants (Raijada et al, 2014). Rapid evaporation of the solvent can lead to the clogging of the nozzle due to the precipitation of the components of the formulation at the nozzle's tip.…”
Section: Before Printingmentioning
confidence: 99%
“…Apart from the casted substrates such as orodispersible thin films or SOFTs, commercially available edible papers, which are often used in the food industry to decorate baked goods and other food products, might be, also, used as printing substrates. Wafer edible sheets and rice papers have been previously used as printing substrates for API-containing inks due to their porous structure and the ability to absorb relatively high amounts of liquid [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that the incorporation of an API within the polymer film affects the mechanical properties of the dosage form. , Therefore, other alternative techniques to produce orally administrable carrier systems have been of interest. In addition, the physical, chemical, and mechanical properties of these matrices need to be optimized for the fabrication of inkjet-printed dosage forms. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Electrospun scaffolds containing APIs in noncrystalline form have been successfully used in intraoral dosage forms. , Furthermore, due to their high surface area and high porosity, electrospun substrate scaffolds are well-suited for printing purposes. , The use of porous substrates can improve the stability of metastable forms of APIs by physical stabilization within the substrate structure . The use of porous substrates helps to avoid problems with increased surface roughness, increases the ease of handling, and improves patient compliance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation